2010
DOI: 10.1111/j.1365-2478.2010.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of alteration at the Millennium uranium deposit in the Athabasca Basin: a comparison of data from two airborne electromagnetic systems with ground resistivity data

Abstract: The Millennium uranium deposit is located within the Athabasca Basin of northern Saskatchewan. The basement rocks, comprised primarily of paleo‐Proterozoic gneisses, are electrically resistive. However, the deposit is associated with highly conductive graphitic metasediments that are intercalated with the gneisses. An unconformity separates the basement rocks from the overlying, horizontally stratified, Proterozoic sandstones of the Athabasca Group (which are also highly resistive). The strike extents of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The work with TEMPEST at the Millennium deposit (Smith et al . ) concluded that this might be possible; the work described in this paper was to see if these conclusions also applied at Midwest.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The work with TEMPEST at the Millennium deposit (Smith et al . ) concluded that this might be possible; the work described in this paper was to see if these conclusions also applied at Midwest.…”
Section: Introductionmentioning
confidence: 90%
“…AEM methods have been tested at the Millennium deposit and show an anomalous response that could be interpreted as due to alteration (Smith et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…The Marker Fault is rooted in graphite-rich pelitic gneisses. The Paleoproterozoic basement rocks in the area belong to the transition zone between the Wollaston and Mudjatik Domains of the Trans Hudson orogeny (Smith et al, 2010). The rocks of the Mudjatik Domain are similar to those of the Wollaston Domain, but the former is dominated by granitic gneisses.…”
Section: Study Areasmentioning
confidence: 97%
“…750 m below the surface along the Marker fault in the basement. Modified afterSmith et al (2010) andWood et al (2012).…”
mentioning
confidence: 99%
“…The principal applications are mining exploration (Smith et al, 2010;Wolfgram and Golden, 2001), subsurface hydrology (Danielsen et al, 2003;Baldridge et al, 2007;Auken et al, 2009;Siemon et al, 2009;Kirkegaard et al, 2011) and on-shore hydrocarbon exploration (Huang and Rudd, 2008;Pfaffhuber et al, 2009). AEM data are often interpreted using apparent conductivity transforms (Wolfgram and Karlik, 1995;Macnae et al, 1998), equivalent plate inversion (Keating and Crossley, 1990;Tartaras et al, 2000;Zhdanov et al, 2002), diffusion velocity analysis (Eaton and Hohmann, 1987), Zohdy's method (Zohdy, 1989;Sattel, 2005) or layered earth inversion (Huang and Palacky, 1991;Chen and Raiche, 1998;Farquharson et al, 1999;Christensen, 2002;Viezzoli et al, 2008;Vallee and Smith, 2009;Guillemoteau et al, 2011).…”
Section: Introductionmentioning
confidence: 99%